Modeling and optimal control of able-bodied and unilateral amputee running - Kleesattel, A. L.; Clever, D.; Funken, J.; Potthast, W.; Mombaur, K. (ISBS Proceedings Archive (Michigan), 2017)
The remarkable performances of amputee athletes in sprint competitions aroused media and scientific interest and led to the question whether running-specific prostheses can be an advantage with respect to able-bodied running. The aim of this study was to bring together motion capture data and Scientific Computing methods to analyze the running motions of an able-bodied and a unilateral transtibial amputee athlete. For each of them a rigid multibody system model was created. By application of optimal control techniques, the dynamics of reference running movements from motion capture data was reconstructed for both models. The able-bodied and the transtibial amputee sprinters rely on dissimilar actuation strategies to perform similar running motions.